2022
DOI: 10.1111/njb.03648
|View full text |Cite
|
Sign up to set email alerts
|

Viola kouliana (Violaceae: section Sclerosium), a new species from India

Abstract: Viola kouliana (Violaceae), a new species from Jammu and Kashmir State, India, is described and illustrated. The species is described and compared with the morphologically related species Viola cinerea and V. behboudiana from which it differs by having puberulous stipules, longer spur, curved style, stigma with unequal discs, an oblong or obovoid capsule which is glabrous and obtuse at apex, containing nine seeds which are 1.4 mm long and smooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Data are available from the Dryad Digital Repository: https:// doi.org/10.5061/dryad.2547d7wxs (Bhellum et al 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Data are available from the Dryad Digital Repository: https:// doi.org/10.5061/dryad.2547d7wxs (Bhellum et al 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…It contains closely related races that are difficult to delimit but differ in distribution, life history traits (annual or perennial), pubescence, and style shape. Nine allopatric taxa have been described [1,150,295,296] but most authorities have interpreted the variation as more or less continuous and have retained only one or two variable species [79,297]. However, a detailed study of the Iranian taxa [91,150] revealed three morphologically discrete species and allopolyploid relationships among them (V. stocksii 4x; V. cinerea 8x; V. behboudiana 8x), which may suggest more taxa warrant recognition within the section.…”
Section: Keymentioning
confidence: 99%